A Fiqh Review of Cash Waqf and Its Implications for the Optimization of Islamic Social Funds: An Analysis of Classical and Contemporary Scholars' Opinions and Its Potential as a Development Financing Instrument - Nabil, Insanul; Alfin, Aidil (ICIEFS Proceeding, 2025)
Cash waqf (waqf al-nuqud) is an important innovation in Islamic social finance that continues to develop and is debated among scholars. Classical scholars, such as those of the Shafi'i school, generally reject the validity of cash waqf because it is considered to not meet the requirement of the waqf object being permanent, while some Maliki and Hanafi scholars and contemporary figures allow it on the condition that the principal fund is maintained and the proceeds are used for the benefit of the community. Contemporary institutions such as the Indonesian Council of Ulama (MUI) and the International Islamic Fiqh Academy (IIFA) support the legality of cash waqf, emphasizing the importance of professional management and transparency. Recent studies show that cash waqf has great potential in raising social funds from the wider community, including those who do not have fixed assets, and can be integrated with other Islamic financial instruments such as zakat and microfinance to support sustainable development, poverty alleviation, and economic empowerment. The implementation of cash waqf in Indonesia and other Muslim countries has shown significant contributions to infrastructure, education, and health development, despite still facing challenges in the form of low public literacy, governance, and sub optimal regulations. Innovations such as Cash Waqf Linked Sukuk (CWLS) and the digitization of cash waqf management are beginning to be adopted to improve effectiveness and accountability. With strengthened regulations, professionalism of nazhir, and public education, cash waqf has the potential to become an inclusive and sustainable development financing instrument in the current and future Islamic social finance ecosystem.